An examination of college freshmen’s food choices - Burbidge, Linda Diane (Kansas State University, 2010)
The prevalence of obesity and overweight has heightened over the last 40 years. Over two thirds of the US adult population is overweight or obese. Further, 18% of adolescents, ages 12 to 19, are obese, which is an increase of over 13% since the late 1970’s. Food environment and peer influence have been emerging areas of study and are thought to be catalysts to unhealthy eating choices. College students present a unique opportunity to look at the impact of a changing food environment, including changes in peer groups. This study is concerned with how students’ peers impact their food consumption and ultimately weight. College freshmen were recruited during their first month on campus at Kansas State University. The students participated in a year-long, three-part study to track their eating habits, weight and height. The students’ parents were also asked to participate by filling out a survey on eating habits. The students also asked one friend they ate with at least once a week to fill out a food record with them. The collected information was transformed into daily average calories for each of six food groups and for macronutrients. A peer ratio was created from the parents and friends calorie intakes to determine the similarity in consumption by each food group or macronutrient. A system of equations was specified and estimated for both food groups and macronutrients. For the food group model, beverages were the only food group with a statistically significant peer ratio term. The coefficient on the ratio was positive, indicating that students would consume more calories from beverages, as their college friends consumed more calories from beverages relative to the students’ parents at home. In the macronutrient model, protein had a statistically significant and positive peer ratio. An examination of the impacts of predicted calories consumed from food groups, along with other individual characteristics, on student’s BMI in the spring term, indicated that increasing snack consumption led to an increase in BMI while increasing bread consumption caused a decrease. Eating more meals at the university dining center also increased BMI. An analysis for the predicted macronutrient values revealed a similar relationship with eating more meals at the dining center, but the predicted macronutrients did not have statistically significant impacts on BMI.
Keywords: College Freshmen; Food Choice; Obesity; Peer Influence; Economics, Agricultural (0503)